Micah 2:9 and the traumatic effects of depriving children of their parents - Boloje, Blessing O. (HTS teologiese studies, 2020)
The Hebrew Bible and/or the Old Testament is replete with narratives of families that are devastated and separated by the unfaithfulness of injustice. Such situations are mostly seen to be theologically reprehensible and morally unacceptable. In the book of Micah, the fluidity of the rhetorical characterisation of those who opposed moral values and the godly voice is manifested in shameful actions against women and children. Since children who are deprived of parents are victims, this article attempts to examine Micah 2:9 and the effects of depriving children of their parents against the background of Israel’s social ethics of the marginalised minority. As a background, the article begins with a description of the family as an attractive and viable setting for the growth and development of children, continues with a relative examination of data on Israel’s social justice and marginalised minority, situates and analyses Micah 2:9 within its context, and then concludes with some effects of depriving children of their parents from the perspective of trauma research.Contribution: This article brings together insight from trauma research into dialogue with biblical, literary, exegetical and theological discourse. Such creative dialogue generates insightful alternative and viable components of the process of creating a healthy, viable community, and consequently invites readers to the urgent ethical concern for compassion and care for the most vulnerable in society.